Possibilities and limitations of cultural studies for rethinking the soviet heritage - A. D. Krivolap (Ukrainian Cultural Studies, 2021)
The article is devoted to the answer to the question how that became possible when culturology was translated into English as Culture studies? There is no danger of losing something in translation, there is a huge conceptual mistake. The work is devoted to the problem of specific cultural forms of adaptation and using terms of culturology. There is a deep and large challenge for social and cultural discourse reflex and explain the difference between culturology and culture studies. The purpose of this text is to describe this academic discourse of culturology and to understand the conditions for the possibility of its existence and underline some differences from culture studies. Culturology was proposed in the western academic tradition but broadly adopted and welcomed in post-Soviet space. Culturology can be understood as a broad social and cultural phenomenon that brings deep consequences to society in transition. The post-Soviet reality can be studied in the frame of postcolonial discourse and culturology will have a chance for new-born again to solve new social challenges. Against the background of serious values about the Soviet past, the critical attitude to Soviet aesthetics does not seem unexpected. Rethinking the Soviet past should begin not with political or economic aspects, but with aesthetic and cultural issues. The discourse of culturology contributes to the creation of a certain vision of the social and physical realities. We will try to consider this process by the example of the approach of culturology to the problem of identity. It is interesting that different visions, what cultural identity is, exist simultaneously. On the one hand, cultural identity is considered as a normative requirement to meet certain socio-cultural requirements, historical ideals that have been tested for centuries and strive for their revival. But, on the other hand, cultural identity is interpreted as an endless process of social formation and the search for answers to new questions and social challenges. The first approach is more typical for culturology, and the second – for culture studies.